2020
DOI: 10.26444/aaem/125394
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A seroprevalence in Erzurum, Turkey

Abstract: Introduction and objective. Hepatitis A Virus (HAV), reportedly the most common cause of acute viral hepatitis in developing countries, infects millions of people worldwide each year. The aim of the study is to investigate the seropositivity of antihepatitis A virus (HAV) IgG and IgM in all age groups in Erzurum, and to determine the effect of various factors such as age, gender, climatic conditions and HAV vaccination (included in 2012 in the National Immunization Schedule on seroprevalence) on the seropositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
3
10
1
Order By: Relevance
“…In terms of acute viral hepatitis A epidemiology, the rate was determined as 0.7% in our study. In recent studies in Turkey, rates were shown as 0.2-1.2% (10,13,19). In this context, the frequency of acute HAV infection in our area is consistent with the studies from Turkey.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In terms of acute viral hepatitis A epidemiology, the rate was determined as 0.7% in our study. In recent studies in Turkey, rates were shown as 0.2-1.2% (10,13,19). In this context, the frequency of acute HAV infection in our area is consistent with the studies from Turkey.…”
Section: Discussionsupporting
confidence: 92%
“…In the study conducted by Kader (29) in Bingöl. In the study conducted by Yılmaz, covering 25007 tests, anti-HAV IgG and IgM positivity were found to be 87.3% and 0.2% in the Erzurum region in 2020 (10). Similar to our study, Yılmaz determined the lowest anti-HAV IgG rates in adolescents and young adults.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Countries classified as the moderately endemic group have seropositivity rates in 90% of the population up to the age of 15 years. 5 , 6 Turkey is classified as moderately endemic group. 6 In India and some countries in Africa, almost all children up to the age of 3 years are seropositive for HAV.…”
Section: Discussionmentioning
confidence: 99%